Predictive Policing: Review of Benefits and Drawbacks - Meijer, Albert; Wessels, Martijn (International journal of public administration, 2019)
This literature review illuminates the conceptualization of predictive policing, and also its potential and realized benefits and drawbacks. The review shows a discrepancy between the considerable attention for potential benefits and drawbacks of predictive policing in the literature, and the empirical evidence that is available. The empirical evidence provides little support for the claimed benefits of predictive policing. Whereas some empirical studies conclude that predictive policing strategies lead to a decrease in crime, others find no effect. At the same time, there is no empirical evidence at all for the claimed drawbacks. We conclude that the current thrust of predictive policing initiatives is based on convincing arguments and anecdotal evidence rather than on systematic empirical research. We urge the research community to do independent tests of both positive and negative expectations to generate an evidence base for predictive policing.